2021
DOI: 10.1108/jed-10-2020-0150
|View full text |Cite
|
Sign up to set email alerts
|

Political institutions and economic performance in Ethiopia: an auto regressive distributed lag bound approach to co-integration

Abstract: PurposeThe main objective of this study is to examine how political institutions affect economic performance in Ethiopia over the 1980–2019 time periods.Design/methodology/approachMainly, the impact of political institution indicators including, level of democracy, political violence, democratic accountability and regime durability have been examined using auto regressive distributed lag (ARDL) bound test approach to co-integration and the error correction model.FindingsThis study confirms that level of democr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…The study of the links between institutions and economic growth in the Democratic Republic of Congo concludes that poor economic policies and conflicts, through their effects on total factor productivity and the investment rate, significantly hampered the economic growth of this S-SA country from 1960 to 2000 (Akitoby & Cinyabuguma, 2004). Another interesting piece of evidence on the role of political institutions in Ethiopia was attained by Garedow (2022), who concluded that the deterioration of political institutions harmfully affected economic performance in Ethiopia between 1980 and 2019. However, based on panel Autoregressive Distributed Lags (ARDL) models, it was identified that level of democracy and democratic accountability had a long adverse effect on economic growth.…”
Section: Institutions In the Economic Development Of S-sa Countriesmentioning
confidence: 99%
“…The study of the links between institutions and economic growth in the Democratic Republic of Congo concludes that poor economic policies and conflicts, through their effects on total factor productivity and the investment rate, significantly hampered the economic growth of this S-SA country from 1960 to 2000 (Akitoby & Cinyabuguma, 2004). Another interesting piece of evidence on the role of political institutions in Ethiopia was attained by Garedow (2022), who concluded that the deterioration of political institutions harmfully affected economic performance in Ethiopia between 1980 and 2019. However, based on panel Autoregressive Distributed Lags (ARDL) models, it was identified that level of democracy and democratic accountability had a long adverse effect on economic growth.…”
Section: Institutions In the Economic Development Of S-sa Countriesmentioning
confidence: 99%
“…However, social entrepreneurship is still characterized by a lack of theoretical frontiers, and it is also confronted by contesting definitions and theoretical models (Sahasranamam and Nandakumar, 2020; García-Uceda et al , 2022b, Aloulou and Algarni, 2022; Vasilev, 2020), the extant knowledge gap and the limitations of empirical data for assessing contextual differences between countries (Canestrino et al , 2020). Indeed, definitions of social entrepreneurship are often multiple and vague: pursuing social aims via marketed-based approaches (Canestrino et al , 2020); encompassing entrepreneurial and innovative activities and services performed by firms with social aims (Diaz-Sarachaga and Ariza-Montes, 2022); tackling social demands that are not satisfied by commercial firms (Sahasranamam and Nandakumar, 2020); creating innovative solutions to address social problems (Rey-Martí et al , 2016; Duong and Antriyandarti, 2021; Garedow, 2021); aligning organizational values with existing societal values to activate support for change (Chatterjee et al , 2021); and using business principles to drive social impacts (Koehne et al , 2022). The multiplicity of definitions often causes misunderstanding about the concept of social entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies contend that institutional quality has an impact on government policies, which in turn affect economic growth [ [16] , [17] , [18] ]. Some others attempt to link institutional quality indicators directly to economic growth [ 16 , [19] , [20] , [21] , [22] ], providing quite varying results. However, while these studies emphasize the importance of strong and better-performing institutions for economic growth, they are heavily biased towards general economic growth [ 20 , [22] , [23] , [24] , [25] ], with little attention paid to the agricultural sector exclusively.…”
Section: Introductionmentioning
confidence: 99%